IRON STATUS OF FIRST YEAR MEDICAL STUDENTS AT GEZIRA UNIVERSITY - MSc, Maha A. Al Siddig; MRCP, Ali B. Habour; Ali Ph.D, Khalid El Tom (Gezira Journal of Health Sciences, 2006)
Objectives:      To determine the iron status of first-year medical students at Gezira University and identify influence of ethnic group and gender on the iron status.  Materials and Methods:  Cross-sectional community based study. The sample consisted of 160 students aged 16-20 years with a mean ( + SD) age 18.56 + 0.94 of both sexes (70 = males, 90 = females). Blood samples were collected from each student and questionnaire was completed. Haemoglobin (Hb), packed cell volume (PCV), serum iron and total iron binding capacity were determined by cyanomethaemoglobin method, microhaematocrit centrifuge and colourmetric methods respectively. Mean corpuscular haemoglobin concentration (MCHC) and transferrin saturation were calculated.  Results: The mean ( + SD) concentration of Hb, serum iron and transferrin saturation of all male students was 14.86 + 1.29 g/dL, 102.46 + 30.5 ^g/dL and 39.72 + 11.23% respectively. The mean ( + SD) concentrations of Hb, serum-iron and transferrin saturation of all female students was 12.57 + 0.92 g/dL, 57.51 + 11.8 ^g/dL and 21.12 + 5.4% respectively.  Haemoglobin level, serum-iron and transferrin saturation were within normal levels according to WHO criteria. There were significant differences between mean values of biochemical parameters and sex of students and father income P < 0.05. There was no significant association between iron status parameters and family size and ethnic groups. There was positive correlation between subject iron status and diet (meat, liver, fruits and hilba).  Conclusion:    Iron status of first-year medical students at Gezira University is within normal reference values. This is in line with the health status of the students.